PENERAPAN METODE PEMBELAJARAN DRILL / LATIHAN DALAM MENINGKATKAN HASIL BELAJAR AKUNTANSI SISWA KELAS XI DI SMA KRAKATAU MEDAN TAHUN PELAJARAN 2013/2014 - Marnoko, Marnoko; Novita , Cindy (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
low accounting learning outcomes of class XII AK students at SMK Swasta Tamansiswa Medan. The purpose of the study was to analyze the effect of the Auditory Intellectually Repetition (AIR) Learning Model on students' thinking skills and learning outcomes in the 2017/2018 academic year. The study was conducted at SMK Swasta Tamansiswa Medan with a total population of 30 class XII AK students, who were also used as research samples (total sampling). The instruments used were a written test of 20 questions (validity and reliability have been tested), an AIR Model questionnaire (10 items), and a thinking ability questionnaire (20 items). The results showed that the AIR Learning Model had a significant effect on students' learning outcomes with a t count of 2.168 > t table 1.70 (sig 0.039 <0.05). In addition, path analysis showed a significant effect of the AIR Model on thinking skills with a value of 0.201 <0.5. Thinking ability also has a significant positive influence on learning outcomes with tcount 2.342 > ttable 1.70 (sig 0.027 < 0.05). The R Square regression value is 0.320 or 32%, indicating that the AIR Model (X1) and thinking ability (X2) contribute to learning outcomes (Y), while 68% is influenced by other variables not studied.